2009
DOI: 10.5194/acp-9-6135-2009
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling the distribution of ozone in the West African lower troposphere during the AMMA (African Monsoon Multidisciplinary Analysis) wet season campaign

Abstract: Abstract. Ozone and its precursors were measured on board the Facility for Airborne Atmospheric Measurements (FAAM) BAe 146 Atmospheric Research Aircraft during the monsoon season 2006 as part of the African Monsoon Multidisciplinary Analysis (AMMA) campaign. One of the main features observed in the west African boundary layer is the increase of the ozone mixing ratios from 25 ppbv over the forested area (south of 12 • N) up to 40 ppbv over the Sahelian area. We employ a two-dimensional (latitudinal versus ver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 76 publications
(81 reference statements)
2
43
0
Order By: Relevance
“…Mean ozone deposition velocites have been measured to be very high in northern Congo Andreae et al, 1992) and in the Republic of Central Africa (Cros et al, 2000). Saunois et al (2009) have shown from measurements of the FAAM BAe-146 aircraft that there is a strong ozone gradient between forest and bare soil in the boundary layer in West Africa. They observed an increase of ozone mixing ratios from 25 ppbv over the forested area up to 40 ppbv over the Sahelian area in the West African lower troposphere.…”
Section: Ozone (O 3 )mentioning
confidence: 99%
“…Mean ozone deposition velocites have been measured to be very high in northern Congo Andreae et al, 1992) and in the Republic of Central Africa (Cros et al, 2000). Saunois et al (2009) have shown from measurements of the FAAM BAe-146 aircraft that there is a strong ozone gradient between forest and bare soil in the boundary layer in West Africa. They observed an increase of ozone mixing ratios from 25 ppbv over the forested area up to 40 ppbv over the Sahelian area in the West African lower troposphere.…”
Section: Ozone (O 3 )mentioning
confidence: 99%
“…The minimum over southern West Africa is related to convective uplift of O 3 -poor air masses from forested regions (high O 3 dry deposition, Saunois et al, 2009) or oceanic regions. Reeves et al (2010) also noted latitudinal differences in ozonesonde data collected in July and August 2006 at Cotonou, Benin (6 • N, 2 • E) and Niamey, Niger (13 • N, 2 • E), further north.…”
Section: Relation To Observed Trace Gas Profilesmentioning
confidence: 99%
“…Comparison with data collected in the lower troposphere can be used as an indicator of convective uplift. Over West Africa during late July/August 2006, lower tropospheric CO varied from 145 ppbv over southern tropical forests to 80-90 ppbv north of 14 • N (Saunois et al, 2009;Reeves et al, 2010). An analysis of all aircraft vertical profile data collected during July-August 2006 showed a maximum in CO concentrations in the upper troposphere (200 hPa) and that flights influenced by local convection had more variable CO ranging from 80 to 200 ppbv compared to "non-convective" flights (100-150 ppbv).…”
Section: Relation To Observed Trace Gas Profilesmentioning
confidence: 99%
“…West Africa is characterized by the presence of potentially important and poorly known sources of aerosol and ozone precursors. Large latitudinal variability of nitrogen oxides emissions in West Africa during the wet season was observed during AMMA and is reported by Stewart et al (2008); NO x levels in the Sahelian area are high leading to higher ozone mixing ratios (Saunois et al, 2009) while ozone precursors from biomass burning in the southern hemispheric African continent can be transported by deep convection in the upper troposphere up to 10 • N (Mari et al, 2008;Real et al, 2010).…”
mentioning
confidence: 99%